Elizabeth A. Sutton, Capitalism and Cartography in the Dutch Golden Age - Storm, Reinder (BMGN - Low Countries Historical Review, 2017)
Elizabeth A. Sutton, Capitalism and Cartography in the Dutch Golden Age (Chicago / London, The University of Chicago Press 2015, 184 pp., isbn 9780226254784).